Mechanics of creep brittle matereials 2 - Cocks, A. C. F.; Ponter, A. R. S.; International Colloquium "Mechanics of Creep Brittle Materials 2" (1991 : University of Leicester) (London : Elsevier Applied Science, 1991)
09